Forms and signs of the Ukrainian national costume and their use in modern clothing design - Hryhorova, larysa (Professional Art Education, 2022)
The purpose of the article is to reveal the significance of the national Ukrainian costume as a creative source for the modernization of existing techniques of form formation in modern clothing design.Methods & methodology. The analysis of Ukrainian folk and modern costume was carried out in a combination of several methods important for understanding the components of the research subject – art history, cultural, concrete historical, comparative-historical and design analysis.Scientific novelty is determined by the degree of use of folk traditions for modern clothes modeling; creation of collections based on folk costume; possibilities of borrowing of the traditional folk costume in modern conditions and in future. The historical experience of using elements of the Ukrainian national ornament in the collections of most domestic and foreign designers is analyzed and specified. Two directions of using the forms and features of the Ukrainian national costume in modern clothing design are distinguished: 1) the ornament invariably appears as part of the decorative structure of the costume, sometimes acquiring the status of a compositional center; 2) the ornament element is not part of the decorative structure of the costume but is the basis of the silhouette form itself. The practical experience of using elements of traditional decorative and applied art by students (future designers) is singled out, which gives modern clothing collections aesthetic expressiveness, originality, man-madeness and contributes to the development of national artistic culture.Results. The national costume is a special object of creative activity of the designer. The art of creating a costume in an ethnic style requires skill, knowledge, imagination, taste, and certain skills from the creator. The elements used by modern designers are becoming more and more stylized, but they do not lose their appeal because folk art hides the unity of man and nature, which helps creators create new images. The idea of using the Ukrainian costume in the creation of modern clothes is not new, since the first half of the 20th century, the folk costume, its cut, ornament, and color combinations have been widely used by fashion designers in the design of clothes. The need and importance of preserving and developing traditions in the structure of national culture was noted, as well as the possibilities of using folk motifs in the creation of both designer clothes and mass production. The importance of folk costume art as a creative source is highlighted. The relevance of designing and manufacturing a modern costume based on the study of the national heritage of Ukraine is substantiated. The design of a modern suit cannot develop in isolation from national traditions. It is quite important to preserve and develop traditions in the structure of national culture, as well as to determine the possibilities of using folk motifs in the creation of both designer clothes and mass production.
Keywords: folk costume; clothing design; collection; design; ornament; form